2020
DOI: 10.3390/diagnostics10060376
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Breath-Hold Compressed-Sensing 3D MR Cholangiopancreatography at 3T: Image Quality Analysis and Clinical Feasibility Assessment

Abstract: Magnetic resonance cholangiopancreatography (MRCP) has been widely used in clinical practice, and recently developed compressed-sensing accelerated MRCP (CS-MRCP) has shown great potential in shortening the acquisition time. The purpose of this prospective study was to evaluate the clinical feasibility and image quality of optimized breath-hold CS-MRCP (BH-CS-MRCP) and conventional navigator-triggered MRCP. Data from 124 consecutive patients with suspected pancreaticobiliary diseases were analyzed by two radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…Note that, unlike our study, both sequences were acquired using free-breathing navigator-triggered method and the two sequences acquisition parameters differed only for the acceleration factor and repetition time [23]. In Song et al's study, a significantly better CBD to PTB tissues CR was achieved using an optimized BH-CS-MRCP sequence compared to conventional MRCP (0.99 ± 0.01 versus 0.94 ± 0.04, p < 0.001), with slightly higher CR values compared to our study for both sequence [32].…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Note that, unlike our study, both sequences were acquired using free-breathing navigator-triggered method and the two sequences acquisition parameters differed only for the acceleration factor and repetition time [23]. In Song et al's study, a significantly better CBD to PTB tissues CR was achieved using an optimized BH-CS-MRCP sequence compared to conventional MRCP (0.99 ± 0.01 versus 0.94 ± 0.04, p < 0.001), with slightly higher CR values compared to our study for both sequence [32].…”
Section: Discussioncontrasting
confidence: 56%
“…Another optimized CS-BH-MRCP sequence at 3T with decreased accelerator factor and a reduced FOV and matrix without changes in spatial resolution, was proposed by Song et al, and demonstrated comparable or even better image quality than conventional MRCP [32]. Overall, the MPD was also better visualized with the optimized sequence [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although BH-CS-MRCP has shown great potential as an alternative method of RT MRCP, earlier studies using BH-CS-MRCP have reported several issues, such as inferior background signal suppression and lesser visibility of small ductal structures similar to GRASE-MRCP. However, we used an optimized BH-CS-MRCP with a smaller FOV and reduced acceleration factor, which was proven to be equally good or even better than conventional MRCP [ 27 , 28 ]. Some caution is needed when interpreting our study results because a recent study comparing BH-CS-MRCP and BH-GRASE-MRCP using the same MR machine with a BH time of 16–20 s showed no significant difference in image quality except for background suppression [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, an MR technique using accelerated compressed sensing (CS) with a sparsity-based reconstruction of extremely undersampled data has been developed and has demonstrated much potential in making MR data acquisition faster [ 8 , 9 ]. Several recent studies have proven its clinical value in 3D MRCP sequences, enabling single BH-MRCP with comparable or even better image quality compared with conventional 3D-RT-MRCP [ 10 , 11 ]. Thus, we hypothesized that SSFSE combined with a CS technique (SSFSE CS ) can produce comparable or even better image quality than that of conventional T2 sequences including multishot TSE (mTSE) and conventional SSFSE (SSFSE CONV ) with an even shorter acquisition time.…”
Section: Introductionmentioning
confidence: 99%